Проблема использования партисипативного подхода на уроках физической культуры в средней школе - Артюхова, Т.В. (My University, 2013)
This article considers participation as one of conditions of efficiency of the teaching and educational process constructed on understanding of pupils as the free, complete, creative person, capable in process of increase of the level to professional interaction with teachers.